2020
DOI: 10.1080/17522439.2020.1773910
|View full text |Cite
|
Sign up to set email alerts
|

Clinical correlates of hearing voices among people seeking interventions for dissociation: a cross-cultural investigation

Abstract: A. Ross (2020) Clinical correlates of hearing voices among people seeking interventions for dissociation: a cross-cultural investigation,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
5
0
1
Order By: Relevance
“…For example, measures of trauma-related voices should not only assess the number of voices, the frequency, loudness, duration, location, and clarity of voices, as well as the interference, distress, and emotional impact of voices, they should also assess the frequency and strength of both positively and negatively valenced voices to improve content validity. Similarly, although existing measures assess the frequency in which people comply with the demands of voices (e.g., Leishout & Goldberg, 2007), some trauma-affected individuals perceive voices to take command of their body (Fung et al, 2020), and future measures should be adapted to capture the full range of compliance-like behaviour.…”
Section: Methodological Recommendationsmentioning
confidence: 99%
“…For example, measures of trauma-related voices should not only assess the number of voices, the frequency, loudness, duration, location, and clarity of voices, as well as the interference, distress, and emotional impact of voices, they should also assess the frequency and strength of both positively and negatively valenced voices to improve content validity. Similarly, although existing measures assess the frequency in which people comply with the demands of voices (e.g., Leishout & Goldberg, 2007), some trauma-affected individuals perceive voices to take command of their body (Fung et al, 2020), and future measures should be adapted to capture the full range of compliance-like behaviour.…”
Section: Methodological Recommendationsmentioning
confidence: 99%
“…Having said that, the differences between CPTSD and PTSD were not significant in our sample, which is possibly due to the small number of participants in the PTSD group. Previous studies have also shown that psychotic symptoms are not rare among people with trauma-related psychopathology (58,59). Therefore, when a client presents with severe depression or psychotic symptoms, trauma disorders should be considered as possible comorbid conditions.…”
Section: Discussionmentioning
confidence: 94%
“…To test these hypotheses, we analyzed baseline data from two studies that evaluated web-based psychoeducation for people seeking interventions for dissociation. The two studies, including the methodology, sample characteristics and measures, have been reported elsewhere (for the details, see Fung et al (2020b)). Both studies were approved by the Human Subjects Ethics Sub-committee of the Hong Kong Polytechnic University.…”
Section: Participantsmentioning
confidence: 99%